2014
DOI: 10.1016/j.pbb.2014.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of non-nicotine tobacco constituent compounds on nicotine self-administration in rats

Abstract: Tobacco smoking has been shown to be quite addictive in people. However, nicotine itself is a weak reinforcer compared to other commonly abused drugs, leading speculation that other factors contribute to the high prevalence of tobacco addiction in the human population. In addition to nicotine, there are over 5000 chemical compounds that have been identified in tobacco smoke, and more work is needed to ascertain their potential contributions to tobacco’s highly addictive properties, or as potential candidates f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 40 publications
4
41
0
Order By: Relevance
“…17 Myosmine itself has not been evaluated for self-administration; however, myosmine doses of 0.02-2 mg/kg did not affect nicotine self-administration. 18 The present results demonstrate that, while the effects of cotinine and myosmine on locomotor activity are more similar to each other than to those of nicotine, the pharmacological profiles also differ, in that higher doses of myosmine (10-50 mg/kg) produced signs of malaise (e.g., flattened body posture, ptosis) whereas cotinine at doses up to 50 mg/kg did not alter overt behavior.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…17 Myosmine itself has not been evaluated for self-administration; however, myosmine doses of 0.02-2 mg/kg did not affect nicotine self-administration. 18 The present results demonstrate that, while the effects of cotinine and myosmine on locomotor activity are more similar to each other than to those of nicotine, the pharmacological profiles also differ, in that higher doses of myosmine (10-50 mg/kg) produced signs of malaise (e.g., flattened body posture, ptosis) whereas cotinine at doses up to 50 mg/kg did not alter overt behavior.…”
Section: Discussionsupporting
confidence: 52%
“…self-administration procedures, but was not reinforcing itself. [18][19][20] In summary, nicotine, cotinine, myosmine and anatabine produced distinctive patterns of effects on locomotor activity that were timeand dose-dependent. Nicotine and cotinine proved to be the most potent constituents (with lowest effective doses of 0.1 mg/kg) whereas the lowest effective doses of anatabine and myosmine were 1 mg/kg and 10 mg/kg, respectively.…”
Section: Discussionmentioning
confidence: 87%
“…Catheters were surgically implanted into the right jugular veins of each animal in the manner as previously described (Hall et al , 2014). Briefly, animals were anesthetized with a combination of ketamine (60 mg/kg i.p.)…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies have shown that nonnicotine components in tobacco are also reinforcing or influence nicotine SA. Anabasine dose dependently increased nicotine SA at 0.02 mg/kg s.c. in rats, whereas both anabasine and anatabine reduced nicotine SA at 2 mg/kg s.c. (Hall et al, 2014). Another non-nicotine tobacco component, norharmane, was behaviorally reinforcing on its own, and these reinforcing effects were additive with those of nicotine (Arnold et al, 2014).…”
Section: Nicotinementioning
confidence: 99%